PENGARUH PEMBERIAN AROMATERAPI JAHE TERHADAP PENURUNAN HIPEREMESIS GRAVIDARUM PADA IBU HAMIL TRIMESTER I DI WILAYAH KERJA PUSKESMAS LIMBOTO - Ani Retni; Haslinda Damansyah (Jurnal Inovasi dan Terapan Pengabdian Masyarakat, 2022)
Changes that occur in pregnant women can cause discomfort in pregnancy, one of which is nausea and vomiting. Nausea and vomiting or hyperemesis gravidarum is one of the complications of pregnancy. The purpose of research was to determine the effect of ginger aromatherapy on reducing hyperemesis gravidarum in first trimester pregnant women. This type of research was comparative analytic with a quasi-experimental one grup pre-post design. The population were 20 respondent. The sampling technique used was total sampling technique. The result showed there was an effect of ginger aromatherapy on reducing hyperemesis gravidarum in first trimester pregnant women with p-value = 0.000. So it can be concluded, there is an effect of giving ginger aromatherapy to reduce hyperemesis gravidarum in first trimester pregnant women in the working area of the Limboto Health Center. This research is expected to provide additional knowledge and experience for researchers in carrying out the task of providing nursing care services to the community.